First Case of Human Rabies in Chile Caused by an Insectivorous Bat Virus Variant - Favi, Myriam (Centers for Disease Control and Prevention, 2002)
The first human rabies case in Chile since 1972 occurred in March 1996 in a patient without history of known exposure. Antigenic and genetic characterization of the rabies isolate indicated that its reservoir was the insectivorous bat Tadarida brasiliensis. This is the first human rabies case caused by an insectivorous bat rabies virus variant reported in Latin America.